PAIN OF PAYING AS MEDIATION: AN ANALYSIS OF THE INFLUENCE OF DIGITAL PAYMENTS AND FINANCIAL LITERACY ON STUDENTS' IMPULSE BUYING BEHAVIOR - Muhammad Yahfi; Mohammad Mas'ud said; Khoiriyah Trianti (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study analyzes the influence of digital payment usage and financial literacy on impulsive buying behavior, with pain of paying as a mediating variable. This topic is important due to the high adoption of digital payments among Generation Z, which potentially reduces psychological control during transactions and encourages consumptive behavior. The research aims to investigate whether digital payment usage and financial literacy influence impulsive buying, as well as the mediating role of the pain of paying in this relationship. Using a quantitative approach, a survey was conducted with 100 students at the Islamic University of Malang. The data were analyzed using PLS-SEM with SmartPLS 4. The results indicate that digital payment usage has a significant positive effect on impulsive buying, while financial literacy has a significant negative effect. Furthermore, the pain of paying partially mediates the effect of digital payment usage on impulsive buying, but does not mediate the relationship between financial literacy and impulsive buying. In conclusion, digital payments encourage impulsive buying by reducing the pain of paying, whereas financial literacy directly strengthens consumption control without involving the pain of paying. These findings contribute to the theory of digital consumer behavior and highlight the importance of financial literacy programs in the context of digital transactions